A Critique of Pure Linguistic Reason: Kantian Remarks on Prolegomena to a Theory of Language - Mehdi Safaie-Qalati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Prolegomena to a Theory of Language, the main work of Louis Hjelmslev, is an account of his “Glossematics” which is a complex formal theory about the nature of linguistic knowledge and the structure of human understanding in general. The current paper starts with a brief evaluation of a newly released Persian translation of this work; the problem triggering a hermeneutic interpretation of Hjelmslev’s theory in the light of Kant’s “pure reason” in the second part of the current paper is a claim about the potentials of “Glossematics” to be revived as an operational theory of linguistic epistemology in the current mainstream of Linguistics. I have shown that, like any other structural theory of human understanding, basing the “necessity” of the formal propositions of “Glossematics” on the notion of “structure” is the theory’s Achilles heel making this initially intended “self-contained” theory change into a paradoxically “transcendental” epistemology. This transcendence in turn, puts Glossematics in the same boat with Nativist epistemological schools, which are all vulnerable to similar challenges. In conclusion, Hjelmslev’s theory of “Glossematics” is shown to be another “Objectivist” theory that is ruled out by the current findings in Cognitive Sciences.